Walkability Index Based on Pedestrian Needs in the Losari Beach area of Makassar City - Susy Asteria Irafany1, Shirly Wunas2, Slamet Trisutomo3, Arifuddin Akil4, Mimi Arifin5, Abd. Rachman (Institute of Medico-legal Publications Pvt Ltd, 2020)
Walkability Indexis the result of measuring the comfort level of pedestrian paths which will be a benchmarkfor developing pedestrian paths that are feasible for everyone. Jpedestrian paths (sidewalks) can be saidto be feasible if they can meet pedestrian needs based on several criteria such as accessibility, circulation,safety, security, beauty, cleanliness, noise, shade, and connectivity. The purpose of this study is to obtaina pedestrian comfort index based on pedestrian needs in the Losari Beach Area and Fort Rotterdam. Toproduce this comfort index, it is necessary to identify the factors and measure the level of comfort based onpedestrian needs, and to determine the priority of pedestrian needs..The pedestrian path available in this areais known as “Bundaratta”, located in the recreation/natural tourism area (Losari Beach) and cultural tourism(Fort Rotterdam) people of Makassar City. With the function of the land as a recreation area, a comfortablepedestrian path is urgently needed by local and foreign tourists to enjoy and reach the existing facilitiesaround the area. This research is a quantitative descriptive study, using a Likert scale to obtain a level ofcomfort and the Analytical Hierarchy Process (AHP) to obtain priority for the comfort factor. The resultsshowed that the pedestrian comfort index along Losari Beach to Fort Rotterdam is 60.20 and it is in thecomfortable category, but it still needs some repairs and improvements in several location segments so thatthis pedestrian lane falls into the category that is truly comfortable and even very comfortable. for its users.